Poetry and tales - Poe, Edgar Allan (The Library of America, 1984)
This book is a refreshing reclamation of class and importance. Indeed, one rarely finds a volume more indicative of artistic essence, or more faithful to the memory of great literary genius than this unassuming compendium. Moreover, "Poetry, Tales, and Selected Essays" demonstrates a peerless selection of Poe's greatest work. The seasoned Poe-reader will find cause, after sufficient perusal, to conclude that few works are able to illustrate Poe in so honest a light